A Qualitative Study To Explore The Lived Experiences Of Single Mother Residing At Sangli Miraj Kupwad Corporation Area - Firoj Valandkar, Anjum; Kulkarni, Sunil M.; Jadhav, Vaishali; Kumar Ray, Suresh; S. Deshmukh, Parshuram (Journal of Neonatal Surgery, 2025)
The purpose of this study is to explore the lived experiences of single mother residing at Sangli Miraj Kupwad corporation area. Method: Qualitative , phenomenological research approach was used. Saturation of data was achieved with 12 samples. Non probability purposive sampling method was used. The setting was Sangli Miraj Kupwad corporation area. The data was collected through one to one in-depth guided interview. Results: A thematic analysis was utilized based on the Collaizis method to assess the collected data. Based on commonalities within the data, themes and categories were formulated. Theme no.1: Physical experiences of single mother with sub themes as fatigue and inadequate food intake. Theme no.2: Psychological experiences of single mother with sub themes as stress, psychological comfort and managing loneliness. Theme no.3: Social experiences of single mother with sub themes as Cooperation, Participation in Social function, decrease interaction in social functions, social blaming. Theme no.4: Financial experiences of single mother with sub themes as financial hardships, managing financial matters. Theme no.5: Spiritual practices of single mother with sub themes as faith. Conclusion: The results will assist in providing single mothers with counselling services and in identifying and resolving the issues that these mothers were faced.